Calculating possibility of the leaf area index of apple and pear trees - Riczu, Péter; Tamás, János (Acta Agraria Debreceniensis, 2012)
A significant proportion of the aboveground green and dry weight of the plant constitutes the foliage. The canopy is an important factor of plant growth. On one hand the canopy absorbs the solar energy, which is necessary for the photosynthesis, on the other hand accumulates the absorbed nutrients by the roots, and the most of the water-loss happens through the foliages. The determination of the full canopy is not an easy target. In our research we developed a measurement method to determine the leaf area. With the parameters of the examined tree (leaf length and maximum width) and the data of ADC AM 100 leaf area scanner we determined the k-value, with which we can easily and fast evaluate the leaf surface.